Expectations data in structural microeconomic models - Gizem Koşar; Cormac O'Dea (Federal Reserve Bank of New York, 2022)
A growing literature uses now widely available data on beliefs and expectations in the estimation of structural models. In this chapter, we review this literature, with an emphasis on models of individual and household behavior. We first show how expectations data have been used to relax strong assumptions about beliefs and outline how they can be used in estimation to substitute for, or as a complement to, data on choices. Next, we discuss the literature that uses different types of expectations data in the estimation of structural models. We conclude by noting directions for future research.
Keywords: D84; D15; C51; C13; D83; 330; expectations data; beliefs; household surveys; structural models; hypotheticals; choice expectations; stated-preference data; Erwartungsbildung; Strukturmodell; Offenbarte Präferenzen; Theorie